The spectrum of Evans syndrome: a literature review - Maqsood, Hamza; Shakeel, Hassan Abdullah; Gulraiz, Azouba; Khan, Muhammad Dilawaer (International Journal of Research in Medical Sciences, 2020)
Evans syndrome (ES) is an autoimmune disorder characterized by the simultaneous or sequential development of autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP) and/or immune neutropenia in the absence of any underlying cause. Evans syndrome is a rare disorder although the exact frequency is unknown. No sex predilection is known and Evans syndrome has been described in all ethnic groups and at all ages. Classification of ES includes primary, with this being an exclusion diagnosis with no underlying condition, and secondary in the presence of an underlying disease. Clinical features are associated with anemia and thrombocytopenia including pallor, weakness, fatigue, jaundice, petechiae, ecchymosis, gingivorrhagia and epistaxis. First, a detailed history must be taken from the patient to determine the risk factors for developing ES then a family history of immune disorders along with a thorough physical examination. The management of Evans syndrome remains a challenge. Steroids with and without IVIG are recommended as front-line therapy. Red blood cell/platelet transfusion is indicated only in severe symptomatic patients due to the risk of exacerbations. Splenectomy may also be considered a second-line treatment.